2016
DOI: 10.21010/ajtcam.v13i3.22
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Extraction Parameters of Theabrownin From Sichuan Dark Tea

et al.

Abstract: Background: Sichuan Dark Tea is a popular beverage with hypolipidemic and lifting greasy properties in the minority neighborhoods of Sichuan and Tibet regions. The theabrownin, an important pigment of dark tea, has been proven for the role of the hypolipidemic property in Sichuan Dark Tea. The objective of the study investigated the extraction process of theabrownin. Materials and Methods: Theabrownin was extracted from Sichuan Dark Tea with water and organic solvents. The quadratic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…As mentioned in previous studies, theaflavins (TFs) and thearubigins (TRs), the two main bioactive compounds in tea, are oxidized to theabrownin (TB) during the fermentation process [ 12 ]. It is also known that theabrownin is a typical component of Pu-erh tea, so it may be its bioactive substance for lowering cholesterol and blood lipid levels [ 13 , 14 ]. Previous studies revealed that the bioactive compounds in Pu-erh tea are theabrownin and gallic acid during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in previous studies, theaflavins (TFs) and thearubigins (TRs), the two main bioactive compounds in tea, are oxidized to theabrownin (TB) during the fermentation process [ 12 ]. It is also known that theabrownin is a typical component of Pu-erh tea, so it may be its bioactive substance for lowering cholesterol and blood lipid levels [ 13 , 14 ]. Previous studies revealed that the bioactive compounds in Pu-erh tea are theabrownin and gallic acid during fermentation.…”
Section: Introductionmentioning
confidence: 99%